Flour lab : an at-home guide to baking with freshly milled grains - Leonti, Adam; Parla, Katie (Clarkson Potter/Publishers, 2019)
In Flour Lab, the new definitive book on flour, chef Adam Leonti shows you the best tools and techniques for making flour that is better-tasting and more nutritious than pre-ground flours. He gives expert tips on where to source wheat, how to mill at home, and how to work with different grains. Here, too, he specifically addresses the idiosyncrasies of working with freshly milled flour as opposed to what's found on supermarket shelves. Twenty recipes for breads, pasta, pizza, cakes, and pastries serve as a practical instruction for using fresh flour in a variety of ways.